Yam pectin and textural characteristics: a preliminary study - Effah-Manu, L.; Maziya-Dixon, Busie; Wireko-Manu, F.D.; Agbenorhevi, J.K.; Oduro, I. (Informa UK Limited, 2022)
The texture of yams is a key determinant in the selection of yams for boiled and pounded yams. This study was conducted to quantify pectin from local and newly developed yam varieties and to correlate pectin and its degree of esterification (DE) with instrumental textural profile parameters of boiled and pounded yam. Isolation of pectin from yam cell wall material (CWM) was achieved with citric acid and the degree of esterification (DE) was determined. The textural parameters were obtained using a texture analyzer. All the new D. rotundata (Poir) varieties had low CWM which varied from 11.88 to 18.95% compared to the D. alata varieties which ranged from 27.60 to 32.79%. Pectin yield (%) for CRI D. alata varieties ranged from 4.47 to 11.35 while CRI D. rotundata (Poir) varieties ranged from 5.18 to 5.50%. Generally, CRI D. alata yam varieties had higher pectin than D. rotundata (Poir) varieties. The DE for all samples ranged from 22.54 to 51.37%, making yam pectin low methoxy. Positive correlations existed between the textural parameters and pectin content as well as the DE but were not significant (p > .05). This study shows that low methoxy yam pectin has no effect on textural characteristics of boiled and pounded yam.